Description Of Blood Sugar Levels In Diabetes Mellitus Patients Who Have A Smoking Habit In Tambakrejo Bojonegoro - Susanti, Dwi Agung; Mulyani, Sri; Utami, Wiwik; Widyaningsih, Vania (Jurnal EduHealth, 2022)
Modern lifestyles with choices food menu and unhealthy ways of life are increasingly spreading to levels of society, causing an increase in the number diabetes mellitus, a phenomenon in the Working Area Tambakrejo, where most people with diabetes mellitus have smoking habits. The purpose of the study was to identify blood sugar levels in people with diabetes mellitus who have a smoking habit. This type of research is descriptive with descriptive survey approach. The population of all young couples is 345 respondents, with a total sample of 117 respondents, sampling using non-probability sampling with accidental sampling technique. Collecting data by observing the results of blood sugar while then in editing, coding, scoring, tabulating and presenting the results. The results showed that more than some respondents had abnormal sugar levels 80 people (68.4%) and less than some respondents had normal sugar levels 37 people (31.6%). The conclusion is that more than half of the blood sugar levels in people with diabetes mellitus who have a smoking habit in the Working Area Tambakrejo Bojonegoro are not normal. Can add information and insight related to blood sugar levels in people with diabetes mellitus can be a motivation for behave in a healthy life.